2013
DOI: 10.1038/ng.2506
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide association analyses identify multiple loci associated with central corneal thickness and keratoconus

Abstract: Central corneal thickness (CCT) is associated with eye conditions including keratoconus and glaucoma. We performed a meta-analysis on >20,000 individuals in European and Asian populations that identified 16 new loci associated with CCT at genome-wide significance (P < 5 × 10−8). We further showed that 2 CCT-associated loci, FOXO1 and FNDC3B, conferred relatively large risks for keratoconus in 2 cohorts with 874 cases and 6,085 controls (rs2721051 near FOXO1 had odds ratio (OR) = 1.62, 95% confidence interval (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

32
322
3
6

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 275 publications
(363 citation statements)
references
References 53 publications
(86 reference statements)
32
322
3
6
Order By: Relevance
“…The authors concluded that these findings demonstrated that part of the genetic predisposition to KC is mediated through genes underlying CCT, with the remaining predisposition attributable to alternative mechanisms. 91 This conclusion mirrors the clinical finding that the occurrence of a relatively thin cornea in isolation is distinct from the progressive regional thinning of the cornea that is a feature of KC.…”
Section: Geneticssupporting
confidence: 66%
See 1 more Smart Citation
“…The authors concluded that these findings demonstrated that part of the genetic predisposition to KC is mediated through genes underlying CCT, with the remaining predisposition attributable to alternative mechanisms. 91 This conclusion mirrors the clinical finding that the occurrence of a relatively thin cornea in isolation is distinct from the progressive regional thinning of the cornea that is a feature of KC.…”
Section: Geneticssupporting
confidence: 66%
“…This study identified 16 new loci associated with CCT at genome-wide significance. 91 To investigate whether any CCT-associated loci identified also influence genetic susceptibility to KC, the authors tested for association of these loci in a case-control study including 874 patients with KC. This meta-analysis identified six SNPs that were strongly associated with a risk of KC, within or nearby the following genes/loci; FOXO1, FNDC3B, RXRA-COL5A1, MPDZ-NF1B, COL5A1, and ZNF469.…”
Section: Geneticsmentioning
confidence: 99%
“…27,28 A recent publication describes the criteria for inclusion and exclusion for GLAUGEN, 23 and the details are also available at dbGaP, accession number phs000308.v1.p1. The NEIGHBOR study included 2132 POAG cases and 2290 controls from 12 institutions and also provided data for genetic investigations of central corneal thickness, 29,30 IOP, 31 and POAG. 28 The descriptive information about the design, inclusion/ exclusion criteria, study sites, and collected data in the NEIGHBOR study was recently published.…”
Section: Study Populationmentioning
confidence: 99%
“…A recent study from the International Glaucoma Genetics Consortium (IGGC) identified 16 loci significantly associated with CCT ( Fig. 3) (Lu et al 2013). Pathway analyses suggested that collagen and extracellular matrix pathways are important regulators of CCT (Lu et al 2013).…”
Section: Quantitative Ocular Traits That Are Risk Factors For Glaucomamentioning
confidence: 99%
“…Additionally, genetic variants associated with quantitative ocular traits that are risk factors for common forms of glaucoma have also been identified. These include IOP (van Koolwijk et al 2012), central corneal thickness (CCT) (Vithana et al 2011;Lu et al 2013), and optic nerve parameters including cup-to-disc ratio and optic nerve area (Ramdas et al 2010;Macgregor et al 2010;Axenovich et al 2011) (Table 3). The clinical features of POAG generally include both elevated IOP and optic nerve degeneration.…”
Section: Common Variants Contributing To Adult-onset Glaucoma With Comentioning
confidence: 99%